A qualitative interpretive meta-synthesis of evangelical Christian sex trafficking narratives. Issue 2 (3rd April 2021) - Twis, Mary; Praetorius, Regina
ABSTRACT: The purpose of the present qualitative interpretive meta-synthesis (QIMS) is to explore, categorize, and confront one of the powerful narratives present within the counter-trafficking movement—that of evangelical Christian communities in the United States. The authors focused on the analysis of scholarly ethnographies and autoethnographies (N=7) of the evangelical Christian counter-trafficking culture. The QIMS yielded four themes that can be used to explain and categorize the denouement that is often visible in evangelical sex trafficking narratives, including 1) the perfect victim, 2) sexual objectification, 3) rescue for a greater purpose, and 4) co-optation of narratives. Results of this study point to how laypeople, social workers, and professional activists can shape and promote survivor-centered narratives that more fully advance the human rights of sex trafficking survivors.